Pengaruh Struktur Kepemilikan, Free Cash Flow terhadap Kebijakan Dividen pada Perusahaan Asuransi yang Terdaftar di BEI Tahun 2013-2017 - Deaninda Sekar Pembayun; Subarjo Subarjo (Jurnal Ekonomi Akuntansi dan Manajemen, 2018)
This study aims to find out the Effect of Managerial Ownership Structure (MNJR), Institutional Ownership Structure (INST), Free cash flow (FCF), and the Ownership Structure on Dividend Policy of Insurance Company Registered on the Indonesia Stock Exchange 2013-2017. The population in this study amounted to 55 insurance companies listed on the Indonesia Stock Exchange in 2013-2017. The samples taken were 11 companies with purposive sampling techniques. Hypothesis testing is carried out using multiple linear regression analysis. The results of the study showed that (1) Managerial Ownership Structure does not affect the Dividend Policy as evidenced by the beta coefficient (B) of 0,000, t = -0,064 <t = 2,008, significance probability of 0,0950> 0,05 (2) ownership structure Institutional effect on Dividend Policy is proven by beta coefficient (B) of 0.020, t = 3.053> t = 2.008 and significance probability value of 0.004 <0.05 (3) Free cash flow does not affect Dividend Policy as evidenced by beta coefficient (B) 0,001, t = 1,904 <t = 2,008 and significance probability value of 0,063> 0,05 (4) probability Managerial Ownership Structure, Institutional Ownership Structure, Simultaneous Cash Flow affect the Dividend Policy as evidenced by the value F = 5,031> F = 4,238 , the significance probability value is 0.009 <0.05. Keywords: Managerial Ownership, Institutional Ownership, Free cash flow and Dividend Policy.